1993
DOI: 10.1007/bf02599621
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and medical care utilization among people in the general population who report fatigue

Abstract: The high prevalence of fatigue in the general population appears to be significantly associated with increased lifetime and current risk for affective, anxiety, and somatoform disorders, as well as increased utilization of medical services. These data suggest that assessment of both medical and psychological health may be essential for the proper care of patients with fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 25 publications
7
54
2
2
Order By: Relevance
“…51 Indeed, it was reported that patients identified with fatigue were between six and 10 times more likely to suffer from dysthymia than the population at large. 52 Similarly, fibromyalgia syndrome, which overlaps with CFS, has been associated with major depression and dysthymia. 53,54 Interestingly, fibromyalgia syndrome has been associated with adverse childhood experiences.…”
Section: Symptom and Illness Comorbiditymentioning
confidence: 99%
“…51 Indeed, it was reported that patients identified with fatigue were between six and 10 times more likely to suffer from dysthymia than the population at large. 52 Similarly, fibromyalgia syndrome, which overlaps with CFS, has been associated with major depression and dysthymia. 53,54 Interestingly, fibromyalgia syndrome has been associated with adverse childhood experiences.…”
Section: Symptom and Illness Comorbiditymentioning
confidence: 99%
“…La fatigue devient importante lorsqu'elle atteint un niveau tel qu'elle nuit à la qualité de vie de la personne (Aistars, 1987;Fernsler, 1986;Jamar, 1989;Kurtz, Kurtz, Given et Given, 1993;Skalla et Lacasse, 1992;Walker, Katon et Jamelka, 1993). Selon les écrits, la fatigue perturbe les activités professionnelles, récréatives et sociales, les activités quotidiennes et la capacité à prendre soin de soi-même (Pearce et Richardson, 1996).…”
Section: Contexteunclassified
“…It has been studied in people with various medical disorders such as rheumatic or neurological disorders, malignancies, and other chronic conditions (2, 3). In population-based surveys in Britain and the United States (US), the incidence of fatigue was described to be between 6.0% and 7.5% (4,5). A cross-sectional survey of U.S. workers found the two-week prevalence of fatigue to be 38%, with an estimated annual cost to employers exceeding 136 billion dollars in lost productive work time (6).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional survey of U.S. workers found the two-week prevalence of fatigue to be 38%, with an estimated annual cost to employers exceeding 136 billion dollars in lost productive work time (6). In general, fatigue prevalence ranges from 14% to 25%, depending on demographic, psychological, and social factors in healthy adults (7,8). In chronic conditions, fatigue is the most common disruptive and distressful symptom experienced, and it can have a devastating effect on daily functioning and overall well-being (9).…”
Section: Introductionmentioning
confidence: 99%